Interactive storytelling : 7th International Conference on Interactive Digital Storytelling, ICIDS 2014, Singapore, Singapore, November 3-6, 2014, Proceedings - Fernández-Vara, Clara; Thue, David; Mitchell, Alex (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on Interactive Storytelling, ICIDS 2014, Singapore, Singapore, November 2014. The 20 revised full papers presented together with 8 short papers 7 posters, and 5 demonstration papers were carefully reviewed and selected from 67 submissions. The papers are organized in topical sections on story generation, authoring, evaluation and analysis, theory, retrospectives, and user experience.